Wednesday

March 4, 2015

March 4, 2015

Posted by **Madison** on Tuesday, October 9, 2012 at 12:42am.

f(x)=Square root of 4-x; g(x)=1-3x^2

Show work.

- Math -
**Steve**, Tuesday, October 9, 2012 at 4:45amf(g) = sqrt(4-g) = sqrt(4-(1-3x^2)) = sqrt(3+3x^2)

f(g(2)) = sqrt(3+12) = sqrt(15)

or, g(2) = 1-12 = -11

f(-11) = sqrt(4+11) = sqrt(15)

do g(f) the same way.

**Answer this Question**

**Related Questions**

college algebra - 1. answer the following for the given quadratic function f(x)=...

Calculus - Hi there, I need help with composition of functions. I need to find ...

pre calculus - 1.) If h(x)= (fog)(x) and h(x) = 3 over the square root of x+3 , ...

Math simplifying mixed radicals - Please help me simplify these following mixed ...

math - Nakim simplified 3 times the square root of 2x plus x times the square ...

Composite Functions - f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7) Find: (fog)(x) (...

math - find the functions f&g so that fog = H H(x)=squre root x^2+8 please show ...

Math simplifying mixed radicals - Please help me simplify these following mixed...

Algebra - If f(x)= ln x, g(x) = e^3x, and h(x) = x^7, find the following... a) (...

math - 2.)If f(x)=3x,g(x)=x-3,and h(x)= the square root of x, find (fogox)(X). ...